How boys & girls differ the first six years - Schrank, Louise Welsh; Gray, Leslie; Stage Fright Productions; Learning Seed Company (Lake Zurich, Ill. : Learning Seed, 2002)
Is it all in the genes and chromosomes? Recognizing these differences is essential to understanding child development
Title from title screen
Narrator: Leslie Gray
Keywords: Sex differences (Psychology) in children; Child psychology; Child development